1976
DOI: 10.1182/blood.v47.4.545.545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phorbol myristate acetate on the oxidative metabolism of human polymorphonuclear leukocytes

Abstract: The addition of 0.1 mug/ml of phorbol myristate acetate (PMA) to a suspension of resting human neutrophils causes a marked stimulation of all aspects of cellular oxidative metabolism normally associated with phagocytosis. PMA induces a greatly increased rate of glucose oxidation via the hexose monophosphate shunt, increased production of superoxide anion and of hydrogen peroxide, increased cellular chemiluminescence, and increased iodination of protein material. The time course of hexose monophosphate shunt ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(69 citation statements)
references
References 18 publications
4
64
0
1
Order By: Relevance
“…First, lop6 M athrombin does not activate neutrophils as measured by generation of superoxide anion (Lai, unpublished observation). On the other hand, PMA (the positive control used in the present study; and Shasby et al, 1983) induces superoxide anion and hydrogen peroxide generation from neutrophils (Repine et al, 1974;De Chatelet et al, 1980). In the present study, PMA-activated neutrophils resulted in an increase in endothelial permeability.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…First, lop6 M athrombin does not activate neutrophils as measured by generation of superoxide anion (Lai, unpublished observation). On the other hand, PMA (the positive control used in the present study; and Shasby et al, 1983) induces superoxide anion and hydrogen peroxide generation from neutrophils (Repine et al, 1974;De Chatelet et al, 1980). In the present study, PMA-activated neutrophils resulted in an increase in endothelial permeability.…”
Section: Discussionsupporting
confidence: 43%
“…(5 x lo5 cells) were layered on the endothelium for 10 minutes before the addition of thrombin. In another group of related experiments, neutrophils were added to the endothelial monolayer and were stimulated 10 minutes later with lo-' M phorbol 12-myristate 13-acetate (PMA) (Repine et al, 1974;De Chatelet et al, 1980). The PMA was dissolved in 1 mglml dimethyl sulfoxide and was subsequent diluted in PBS to a final concentration of 200 nglml.…”
Section: Experimental Designmentioning
confidence: 99%
“…Activation of the oxidase through binding of soluble ligands (i.e., fMLP) to surface receptors usually results in O 2 production lasting less than 5 min, whereas receptor-independent activation (i.e., PMA) causes prolonged generation of the O 2 until depletion of necessary substrates and cofactors [332]. Furthermore, in intact cells, the activated oxidase is experiencing a continuous process of activation and deactivation [333].…”
Section: Membranementioning
confidence: 99%
“…PMA has become the most commonly used positive control for oxidase activation [332,338]; however, it is a nonphysiological stimulus. Originally considered to be involved in tumor promotion, although by themselves were not carcinogenic, phorbol esters resulted in many genetic and phenotypic changes, including an increase in oxidase production and the copurification of PKC with the putative phorboid receptor [339 -343].…”
Section: Membranementioning
confidence: 99%
“…Hasui et al reported that a positive correlation exists between phagocytosis and H 2 O 2 production following ingestion of S. aureus [27]. PMA is known to directly activate protein kinase C, bypassing the process of phagocytosis [32]. When stimulated with PMA, addition of IgG did not have any appreciable effect on H 2 O 2 production with PMN of both mature and premature neonates.…”
Section: Discussionmentioning
confidence: 99%